Developing Bioprospecting Strategies for Bioplastics Through the Large-Scale Mining of Microbial Genomes - Vuong, Paton; Lim, Daniel J.; Murphy, Daniel V.; Wise, Michael J.; Whiteley, Andrew S.; Kaur, Parwinder (Frontiers in Microbiology, 2021)
The accumulation of petroleum-based plastic waste has become a major issue for the environment. A sustainable and biodegradable solution can be found in Polyhydroxyalkanoates (PHAs), a microbially produced biopolymer. An analysis of the global phylogenetic and ecological distribution of potential PHA producing bacteria and archaea was carried out by mining a global genome repository for PHA synthase (PhaC), a key enzyme involved in PHA biosynthesis. Bacteria from the phylum Actinobacteria were found to contain the PhaC Class II genotype which produces medium-chain length PHAs, a physiology until now only found within a few Pseudomonas species. Further, several PhaC genotypes were discovered within Thaumarchaeota, an archaeal phylum with poly-extremophiles and the ability to efficiently use CO2 as a carbon source, a significant ecological group which have thus far been little studied for PHA production. Bacterial and archaeal PhaC genotypes were also observed in high salinity and alkalinity conditions, as well as high-temperature geothermal ecosystems. These genome mining efforts uncovered previously unknown candidate taxa for biopolymer production, as well as microbes from environmental niches with properties that could potentially improve PHA production. This in silico study provides valuable insights into unique PHA producing candidates, supporting future bioprospecting efforts towards better targeted and relevant taxa to further enhance the diversity of exploitable PHA production systems.